2013
DOI: 10.1371/journal.pone.0069861
|View full text |Cite
|
Sign up to set email alerts
|

Aging 2.0: Health Information about Dementia on Twitter

Abstract: Online social media is widespread, easily accessible and attracts a global audience with a widening demographic. As a large proportion of adults now seek health information online and through social media applications, communication about health has become increasingly interactive and dynamic. Online health information has the potential to significantly impact public health, especially as the population gets older and the prevalence of dementia increases. However, little is known about how information pertaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 35 publications
6
79
1
1
Order By: Relevance
“…Accordingly, a subgroup of top users, characterized as those with the most followers, inserted links in 92% of their tweets compared to all users with 77%, inserting links in an assessment of Twitter usage to share information about dementia. 19 The amount of links in our study (20%) was slightly lower than in a contemporary Tweet analysis of the AUA and CUA conferences (29%). 4 The vast majority of tweets (88%) took place during scheduled conference hours, with a peak activity of 73 tweets/hour.…”
Section: Discussioncontrasting
confidence: 76%
“…Accordingly, a subgroup of top users, characterized as those with the most followers, inserted links in 92% of their tweets compared to all users with 77%, inserting links in an assessment of Twitter usage to share information about dementia. 19 The amount of links in our study (20%) was slightly lower than in a contemporary Tweet analysis of the AUA and CUA conferences (29%). 4 The vast majority of tweets (88%) took place during scheduled conference hours, with a peak activity of 73 tweets/hour.…”
Section: Discussioncontrasting
confidence: 76%
“…The use of LDA-based health topic modelling topics was explored by Prier et al [21]. Dementiarelated tweets were the focus of work by Robillard et al [22] who collected relevant tweets over a 24h period using keyword filtering and used them to discover the dominant chatter themes. Similarly, Scanfeld et al [25] used Twitter to analyse the patterns of antibiotic use.…”
Section: Related Previous Workmentioning
confidence: 99%
“…Donelle and Booth [22] found that 44.7 % of the breast cancer Facebook groups analyzed for their study were focused on raising funds. Additionally, Twitter has also become a major online social media platform for users to share information [2325]. A study performed by Robillard et al [25] analyzed tweets related to dementia over a 24-h period and found that 77 % of those tweets contained links to health information websites and recent studies involving reducing the risk of dementia.…”
Section: Introductionmentioning
confidence: 99%